2013
DOI: 10.1098/rsbl.2013.0133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant genetic diversity on interactions between higher trophic levels

Abstract: While the ecological consequences of plant diversity have received much attention, the mechanisms by which intraspecific diversity affects associated communities remains understudied. We report on a field experiment documenting the effects of patch diversity in the plant Baccharis salicifolia (genotypic monocultures versus polycultures of four genotypes), ants (presence versus absence) and their interaction on ant-tended aphids, ants and parasitic wasps, and the mechanistic pathways by which diversity influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 15 publications
3
70
0
Order By: Relevance
“…[1 ,2-8,9 ]). Studies have found that plant diversity positively influences arthropod diversity and abundance [3,4,8,10], and alters plant-arthropod and arthropod-arthropod interactions [3,7,11,12]. These findings emphasize that conserving and manipulating plant diversity in natural and managed systems, respectively, is crucial for maintaining ecosystem function [13][14][15].…”
Section: Introductionmentioning
confidence: 94%
“…[1 ,2-8,9 ]). Studies have found that plant diversity positively influences arthropod diversity and abundance [3,4,8,10], and alters plant-arthropod and arthropod-arthropod interactions [3,7,11,12]. These findings emphasize that conserving and manipulating plant diversity in natural and managed systems, respectively, is crucial for maintaining ecosystem function [13][14][15].…”
Section: Introductionmentioning
confidence: 94%
“…Accordingly, there is widespread evidence for positive effects of plant intra-and interspecific diversity on producer biomass influencing arthropod abundance and community structure (Siemann 1998, Crutsinger et al 2006, Cook-Patton et al 2011, McArt et al 2012. Despite increasing recognition for the influence of plant diversity on higher trophic levels, very few studies have addressed the mechanisms for such effects (Raffaelli et al 2002, Moreira et al 2012, Moreira and Mooney 2013. Studies that have looked at the effects of plant diversity on consumers have usually documented broad changes in community structure (Siemann 1998, Crutsinger et al 2006, Johnson et al 2006, Haddad et al 2009, Scherber et al 2010, while comparatively less attention has been given to changes in focal interactions (but see Ninkovic et al 2011, McArt and Thaler 2013, Moreira and Mooney 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing recognition for the influence of plant diversity on higher trophic levels, very few studies have addressed the mechanisms for such effects (Raffaelli et al 2002, Moreira et al 2012, Moreira and Mooney 2013. Studies that have looked at the effects of plant diversity on consumers have usually documented broad changes in community structure (Siemann 1998, Crutsinger et al 2006, Johnson et al 2006, Haddad et al 2009, Scherber et al 2010, while comparatively less attention has been given to changes in focal interactions (but see Ninkovic et al 2011, McArt and Thaler 2013, Moreira and Mooney 2013. As a result, we currently lack a predictive understanding of how plant diversity effects on species interactions scaleup to influence community structure (Johnson 2008), as well as the relative importance of different mechanisms by which plant diversity influences consumers .…”
Section: Introductionmentioning
confidence: 99%
“…35 ha in the University of California San Joaquin Marsh Reserve (33°39′47″N, 117°51′7″W; CA, USA), the same field site where our past studies of this plant have been conducted (Mooney et al 2012b;Moreira and Mooney 2013;Abdala-Roberts et al 2016;Moreira et al 2016;Abdala-Roberts et al 2017). To get distinct genotypes, we collected cuttings from wildgrown plants that were separated by approximately 900 m. Cuttings were dipped in a 20% solution of Dip 'N Grow Root Inducing Concentrate (Dip 'N Grow Inc., Clackamas, OR) and planted in perlite for 6 weeks in a greenhouse.…”
Section: Genotype Selection and Propagationmentioning
confidence: 99%